2018
DOI: 10.3390/nu10111805
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Small Doses of Fructose and Its Epimers on Glycemic Control: A Systematic Review and Meta-Analysis of Controlled Feeding Trials

Abstract: Objective: Contrary to the concerns that fructose may have adverse metabolic effects, an emerging literature has shown that small doses (≤10 g/meal) of fructose and its low-caloric epimers (allulose, tagatose, and sorbose) decrease the glycemic response to high glycemic index meals. Whether these acute reductions manifest as sustainable improvements in glycemic control is unclear. Our objective was to synthesize the evidence from controlled feeding trials that assessed the effect of small doses of fructose and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 84 publications
0
18
0
1
Order By: Relevance
“…Our allulose findings partly align with a recent systematic review and meta-analysis. Although small doses of allulose (8e15 g/ day) failed to reduce HbA 1c in otherwise healthy participants and those who were overweight/obese, the reduction in fasting glucose was approaching significance [76,83,88]. Given that these individuals did not present with hyperglycemia, significant reductions in HbA 1c would not be expected.…”
Section: Findings In the Context Of Previous Literaturementioning
confidence: 95%
See 1 more Smart Citation
“…Our allulose findings partly align with a recent systematic review and meta-analysis. Although small doses of allulose (8e15 g/ day) failed to reduce HbA 1c in otherwise healthy participants and those who were overweight/obese, the reduction in fasting glucose was approaching significance [76,83,88]. Given that these individuals did not present with hyperglycemia, significant reductions in HbA 1c would not be expected.…”
Section: Findings In the Context Of Previous Literaturementioning
confidence: 95%
“…Several systematic reviews and meta-analyses have been conducted to assess the effect of fructose on glycemic control. Two meta-analyses showed that small doses of fructose (up to 50 g/day or 10% of total energy intake/day) in isocaloric exchange for other carbohydrates reduced HbA 1c by~0.4% [82,83]. Evans et al [26] showed that fructose doses of 15 ge100 g isocalorically exchanged for glucose or sucrose in acute trials reduced postprandial glucose and insulin responses without a negative impact on triglycerides, in those with and without type 2 diabetes.…”
Section: Findings In the Context Of Previous Literaturementioning
confidence: 99%
“…According to the systematic reviews and meta-analysis, high doses of fructose (≥ 100 g/day) increases serum TG concentration (10,32), low to middle doses of fructose (0 ~ 90 g/day) have a bene t effect in HbA1c (13,33). But fructose did not increase the risk of hypertension and type 2 diabetes (12,34), also, it did not affect serum HDL-C concentration (32) and cause weight gain when it was substituted for other carbohydrate in diets providing similar calories (35).…”
Section: Discussionmentioning
confidence: 99%
“…Some of them concluded that intakes of fructose were associated with increased risk of obesity, dyslipidemia, and hypertension (8)(9)(10). However, some of them found that a certain dose of fructose has no adverse or even some positive effects on fasting glucose, blood pressure, and blood lipids (11)(12)(13)(14)(15). Most of the studies included in these meta-analyses were interventional studies with high-dose fructose intake.…”
Section: Introductionmentioning
confidence: 99%
“…Allulose is absorbed in the stomach, with peak plasma concentrations of allulose occurring within an Sugar reduction technical challenges hour and the vast majority excreted unchanged in the urine. Allulose has been found to have no impact on blood glucose levels (Noronha et al 2018a); it raises neither blood glucose nor insulin levels in healthy individuals or when consumed by individuals with type 2 diabetes (Noronha et al 2018b). Allulose is nearly calorie-freeit is labelled in the US, for example as having 90% fewer calories than sugar (FDA 2018).…”
Section: Beyond Sweetnessmentioning
confidence: 99%